2021
DOI: 10.1261/rna.077701.120
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive annotation and characterization of planarian tRNA and tRNA-derived fragments (tRFs)

Abstract: tRNA-derived fragments (tRFs) have recently gained a lot of scientific interest due to their diverse regulatory roles in several cellular processes. However, their function in dynamic biological process such as development and regeneration remains unexplored. Here, we show that tRFs are dynamically expressed during planarian regeneration suggesting a possible role for these small RNAs in the regulation of regeneration. In order to characterise planarian tRFs, we first annotated 457 tRNAs in S.mediterranea comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…Around 80% of the tRFs originated from just four tRNAs-tRNA Ala_AGC , tRNA Ala_TGC , tRNA Asp_GTC , and tRNA Arg_TCT . This has been reported in other systems as well (41)(42)(43).…”
Section: Discussionsupporting
confidence: 83%
“…Around 80% of the tRFs originated from just four tRNAs-tRNA Ala_AGC , tRNA Ala_TGC , tRNA Asp_GTC , and tRNA Arg_TCT . This has been reported in other systems as well (41)(42)(43).…”
Section: Discussionsupporting
confidence: 83%
“…The roles of tRDFs are still poorly understood in platyhelminthes, however it was recently reported that they may be involved in the regeneration of planaria (Cao et al, 2020). Interestingly, in these organisms, Piwi proteins and Ago1, but not Dicer or Ago2, were associated with the generation and/ or function of 5'tHFs and 5'tRFs, respectively (Lakshmanan et al, 2021). However, the absence of Piwi genes in all Neodermatans implies that, at least the biogenesis of 5'tHFs could be different in trematodes and cestodes (Fontenla et al, 2017;Fontenla et al, 2021) to those described in free-living flatworms.…”
Section: Evs Pack Homodimeric Trdfs That Could Resist Exonuclease Degradationmentioning
confidence: 99%
“…piRNAs were not detected in Protozoa but were detected in C. elegans and Halichondria panicea , belonging to Nematoda and Porifera [ 14 , 21 ]. In Platyhelminthes, piRNAs were detected in planarians ( Schmidtea mediterranea ) [ 20 ] but were absent in flukes and tapeworms [ 94 ]. Ubiquitously expressed piRNAs were discovered in the soma and germ lines of Annelida, Cnidaria, Echinodermata, Crustacea, Arthropoda, and Mollusca.…”
Section: Discovery Of Pirnas By Srna-seqmentioning
confidence: 99%
“…Next-generation sequencing (NGS) has been widely used for high-throughput characterization of sncRNAs. Increasingly, piRNAs have been discovered in the soma and germ lines of non-model organisms, including Platyhelminthes [ 20 ], Annelida [ 21 ], Cnidaria [ 22 , 23 , 24 , 25 ], Echinodermata [ 26 ], Mollusca [ 27 ], Crustacea [ 28 ], Arthropoda [ 29 ], Reptilia [ 30 ], and Mammals [ 31 ].…”
Section: Introductionmentioning
confidence: 99%